Cellular and molecular mechanisms of xenobiotics-induced premature senescence. Issue 5 (1st October 2020) - Liang, Yuehui; Liang, Ningjuan; Yin, Lirong; Xiao, Fang
Abstract: Premature senescence, which share common features with replicative senescence such as morphology, senescence-associated galactosidase (SA-β-gal) activity, cell cycle regulation, and gene expression, can be triggered by the exposure of various xenobiotics including environmental pollutant, peroxides, and anticancer drugs. The exact mechanisms underlying the senescence onset and stabilization are still obscure. In this review, we summarized the possible cellular and molecular mechanisms of xenobiotics-induced premature senescence, including induction of reactive oxygen species (ROS), tumor suppressors, and DNA damage; disequilibrium of calcium homeostasis; activation of transforming growth factor-β (TGF-β); and blockage of aryl hydrocarbon receptor (AHR) pathway. The deeper understanding of the molecular mechanisms underlying xenobiotics-induced senescence may shed light on new therapeutic strategies for age-related pathologies and extend healthy lifespan. Graphical Abstract: